Preventive effect of Rumex crispus L. on surgically induced intra-abdominal adhesion model in rats - Suntar, Ipek; Demirel, Murside Ayse; Ceribasi, Ali Osman; Ergin, Irem; Gokbulut, Alper (Springer Int Publ Ag, 2021)
Background Rumex crispus L. (Polygonaceae), known as Labada in Turkey, was reported to be used for the treatment of gynecological diseases such as postpartum complications and infertility in folk medicine. Earlier studies on R. crispus have shown that leaf, fruit and root extracts have anti-inflammatory and antioxidant activities and are used for the treatment of tumors in the uterus. The hypothesis of this study is that R. crispus may generate potential anti-adhesive activity against complex factors such as inflammation, oxidation and fibrosis. Objectives We aimed to investigate the potential anti-adhesive activity of aqueous methanol extracts of leaves, fruits and roots of R. crispus. Methods Abdominal adhesion model was performed in 72 female Wistar Albino rats. In the first step of the experiment, the rats were divided into six groups namely, Sham, Control, Reference and Experimental Groups (consisting of three sub-groups in which R. crispus leaf, fruit and root extracts were applied at 100 mg/kg dose). The test samples were administered once to the peritoneal cavity and the rats were sacrificied at the end of the 14th day. Root extract showed prominent activity, therefore this extract was subjected to fractionation to obtain 3 fractions (30-60-100% methanol fractions) by using vacuum-liquid chromatography. In the second stage, animals were divided into 6 groups as Sham, Control, Reference and Experimental Groups (R30, R60, R100 at 100 mg/kg dose). Adhesion scoring, tissue total antioxidant and oxidant levels, histopathological and immunohistochemical (TNF-alpha, IL-6 and IL-8) analyzes were performed. Results and conclusion Adhesion scores, inflammatory cytokines and inflammation cells decreased by the application of R. crispus root extract. The fractions also showed similar anti-inflammatory effects, but R60 was found to be more effective in prevention of intra-abdominal adhesions and uterine fibrosis. R60 fraction, possessing potential bioactivity, was investigated in terms of phenolic composition by HPLC.
Keywords: Rumex crispus; Polygonaceae; Anti-inflammatory; Antioxidant; Anti-adhesive; HPLC